(untitled) (Research, Society and Development, 2021)
Due to the wide scientific divergence of results among in vitro investigations about the influence of food pigmentation on teeth staining during bleaching, this study aims to evaluate in the laboratory the effectiveness of at-home bleaching using carbamide peroxide (CP), and in-office bleaching using hydrogen peroxide (HP) applied to bovine teeth exposed to açaí and guarana energy drink during the dental whitening process. Extracted bovine incisors were randomly separated into six groups as follows: two control groups (at-home bleaching [HB] and in-office bleaching [OB] and immersed in artificial saliva), two groups following the immersion in açaí (HBa and OBa), and two groups following the immersion in guarana (HBg and OBg). The immersion cycle was conducted three times a day for five minutes. After the initial reading, the color was registered subsequently to the third (and last) week of whitening process. This procedure was carried out using Easyshade spectrophotometer and Vita shade guide. The data were submitted to a two-way ANOVA test (p<0.05). The results showed that after three weeks of bleaching, the whitening rate for the OBa group decreased significantly when compared to the other groups, also those submitted to at-home bleaching. After the third week of the whitening process, it was observed that the groups submitted to at-home bleaching presented higher whitening rates than the ones submitted to in-office bleaching. Therefore, the contact with açaí during whitening period may reduce the in-office bleaching efficacy.